Septum pellucidum pilocytic astrocytoma: case report and literature review - Fatima A. Fakhroo; Meshari Almutairi; Salem Baeshen; Othman Almutairi; Hisham Alkhalidi; Abdulrazaj Ajlan (Egyptian Journal of Neurosurgery)
Abstract Introduction Septum pellucidum pilocytic astrocytoma is rare. There are only 3 reported cases in literature. Our patient is the fourth case. Case presentation A 17-year-old male presented with headache. CT brain and MRI brain showed septum pellucidum lesion with obstructive hydrocephalus which looked like colloid cyst. Intraoperatively, the tumor was attached to the lower part of septum pellucidum and it didn’t look like a colloid cyst. Histopathology was pilocytic astrocytoma. Postoperatively, patient recovered well with no neurological deficits or adverse neurological sequalae. Conclusion Septum pellucidum pilocytic astrocytoma should be considered as one of the differential diagnosis of septum pellucidum tumors. We observed that the interhemispheric transcallosal transventricular approach might be associated with lesser comorbidities and neurological deficits in tumors in this location.